2014
DOI: 10.1007/s11605-013-2401-4
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Patient Outcomes After Laparoscopic Anti-Reflux Procedures

Abstract: This study shows that patients had excellent symptom control and low rates of complications and reoperations in long-term follow-up. We found that typical gastro intestinal symptoms responded better compared with atypical symptoms in spite of clear evidence of reflux on preoperative studies. Hiatal hernia was very commonly seen in our patient population and long-term radiographic follow-up suggest that asymptomatic recurrence may be high but rarely requires any surgical intervention. Anti-reflux surgery with c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 16 publications
0
18
0
Order By: Relevance
“…According to preoperative 24-h pH studies and manometry, at least 60 % of these patients will have reflux and/or reduced LES pressure [12]. Simorov et al [13] evaluated 295 patients who underwent laparoscopic AR surgery at one institution, 78 % of which had an associated hiatal hernia. Follow-up at 1 year demonstrated significant improvement in symptoms such as heartburn and regurgitation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to preoperative 24-h pH studies and manometry, at least 60 % of these patients will have reflux and/or reduced LES pressure [12]. Simorov et al [13] evaluated 295 patients who underwent laparoscopic AR surgery at one institution, 78 % of which had an associated hiatal hernia. Follow-up at 1 year demonstrated significant improvement in symptoms such as heartburn and regurgitation.…”
Section: Discussionmentioning
confidence: 99%
“…Follow-up at 1 year demonstrated significant improvement in symptoms such as heartburn and regurgitation. After 3 years, only 16 % reported weekly or daily symptoms of heartburn or regurgitation and the remaining 84 % did not have any of these classic gastrointestinal complaints [13]. A prospective study in 2011 by Furnée et al [14] investigated the benefits of adding an AR fundoplication in large hiatal hernia repair with associated gastroesophageal reflux disease.…”
Section: Discussionmentioning
confidence: 99%
“…It includes patient demographics, operative details, pre-and postoperative patient-rated symptom scores for symptoms commonly associated with PEH, as well as pre-and postoperative pH, manometry, upper gastrointestinal studies (UGI) and endoscopic results. Data are entered into the database at each patient encounter as previously described by Simorov et al [8]. The database was mined for all patients who underwent PEH repair with mesh.…”
Section: Methodsmentioning
confidence: 99%
“…Simorov et al reported data showing many patients remain on PPI after ARS despite being symptom free, and the proportion taking medications increases with time [26].…”
Section: Discussionmentioning
confidence: 99%